Model Pendidikan Agama Kristen Berbasis Teologi: Sinergi antara Gereja dan Amanat Pendidikan - Ema Yolanda Aka; Hagar Magdalena Oujaha; Magdalena Ayang Tura; Sandra Rosiana Tapilaha (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This article discusses the importance of developing a Christian Religious Education (PAK) model based on Christian theology and implemented through the active role of the church in carrying out the Great Commission. True Christian education does not only convey doctrinal information, but also forms the character, spirituality, and calling of the people based on the word of God. The church is positioned as a learning community and the main implementer of the contextual, transformative, and biblical theology-rooted faith education process. Through a qualitative-descriptive approach and literature study, this paper emphasizes that theological foundations, such as God as the source of education, the Bible as the basis of teaching, Christ as the focus, and the church as the implementer, are inseparable elements of PAK. Christian Religious Education based on theology provides clear direction in designing content, methods, and learning objectives that are in line with God's will. Thus, this education model is expected to be able to answer the challenges of the times, strengthen the faith of the congregation, and produce strong and relevant followers of Christ in society.